Applied Relationship between Transport and Economy. Issue 29 (2016) - Limani, Ylber
Abstract: This paper discusses some of the most important issues concerned with the relationship between transport and the economy. The efforts made in this research are specifically focused to achieve the objective of giving some approximate answer to some of the complex questions related to the economic dynamics and transport. Transport is considered to be one of the most influential and vibrant systems of the economy. The transport system is continually changing in time and space, it can be considered as determining factor for economic development and growth. By This research encompasses the mix research methodology combined by qualitative and quantitative research facets. The qualitative research outcomes are then identified and defined factors which determines the relationship between transport and the economy. The quantitative research results are generated figures based on statistical data which provides with the evidence about the real relationship between transport and the economy. The main goal of this research paper is to provide decision makers, planners, and academic spectrum with the thorough explanation of the applied relationship between the transport system and the economic development and economic growth.